Increasing Activity In Group Discussions Through Discovery Learning In Class IV Students - Suyono Suyono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to determine the increase in activity in group discussions in class IV students of SD Negeri 04 Seloromo in science subjects, especially material about changes in the shape of objects. Based on the results obtained during the implementation of class action research it is known that the discovery learning method can increase student activity in group discussions and improve student learning outcomes. In the initial study, only 3 students or 25% completed the KKM in learning. In cycle I it increased to 6 students or 50% who completed KKM. In cycle II, above the KKM 11 students or 92% and 1 student or 8% according to KKM. Thus, it can be concluded that the discovery learning method can increase student activity in group discussions and increase student learning outcomes.